Genome-Wide Identification and Comparison of Cysteine Proteases in the Pollen Coat and Other Tissues in Maize - Li, Yanhua; Niu, Liangjie; Wu, Xiaolin; Faleri, Claudia; Tai, Fuju; Zhang, Man; Liu, Hui; Wang, Wei; Cai, Giampiero (Frontiers in Plant Science, 2021)
Cysteine proteases (CPs), belonging to C1-papain family, play a major role in plant growth and development, senescence and immunity. There is evidence to suggest that pollen CP (ZmCP03) is involved in regulating anther development and pollen formation in maize. However, there is no report on genome-wide identification and comparison of CPs in pollen coat and other tissues in maize. In this study, a total of 38 homologous genes of ZmCP03 in maize were identified. Subsequently, protein motifs, conserved domains, gene structure and duplication patterns of 39 CPs are analyzed to explore their evolutionary relationship and potential functions. The cis-elements were identified in upstream sequence of 39 CPs, especially those that are related to regulating growth and development and responding to environmental stresses and hormones. The expression patterns of these genes displayed remarked difference at a tissue/organ level in maize based on the available transcriptome data in public database. RT-qPCR analysis showed that ZmCP03 was preferably expressed at a high level in maize pollen. Analyses by SDS-PAGE and immunoblot, immunofluorescence and immunogold electron microscopy all validated the cellular localization of ZmCP03 in both pollen coat and pollen cytoplasm. In addition, 142 CP genes from Arabidopsis (Arabidopsis thaliana), rice (Oryza sativa) and cotton (Gossypium hirsutum), together with 39 maize CPs, were retrieved to analyze their evolution by comparing with orthologous genes. The results suggested that ZmCP03 was relatively conservative and stable during evolution. This study may provide a referential evidence on the function of ZmCP03 in pollen development and germination in maize.